Stroke Type, Time to Care, and EWS as Predictors of Patient Outcomes: A Case-Control Study - Megasari, Anis Laela; Wulandari, Ika Subekti (Chakra Brahmanda Lentera Institute, 2025)
Background: Stroke management requires speed in identification and action to improve stroke outcomes. Unfortunately, the identification of strokes is still slow. This study aims to determine the factors that influence the development of stroke patients. Methods: This study used a case-control design with a retrospective approach. This case-control study adheres to the STROBE reporting guidelines. Purposive sampling was applied with a sample size of 37 respondents. The variables studied were the type of stroke, the Early Warning Score (EWS), the time to seek health services, and the outcome of stroke patients. The Glasgow Outcome Scale Extended (GOSE) measures the effects on stroke patients. Spearman and Sommers's test analyzed data to determine the relationship between two variables, and the multiple regression test was used for multivariate analysis. Results: The results showed that the majority of stroke types were Non-Hemorrhagic Strokes (86.5%), the majority of EWS scores fell into the deficient category (51.4%), and the majority of the time spent seeking health services was less than 2 hours (94.6%). There is a significant relationship between the type of stroke (p-value 0.02), EWS score (p-value 0.01), and the time to seek health services and stroke outcome (p-value 0.03). Multivariate analysis revealed that the type of stroke, time to seek health services, and EWS scores were simultaneously or collectively associated with stroke patient outcomes (F count = 5.269 > F table = 2.88, with a coefficient of determination of 32.4%). This research showed that the type of stroke, time to seek health services, and the EWS score can be used as predictors of the outcome level of stroke patients. Conclusion: These findings highlight the importance of integrating Early Warning Score (EWS) into hospital protocols to support early recognition and timely response for stroke patients, potentially improving patient outcomes